2000
DOI: 10.1016/s0014-5793(00)01785-3
|View full text |Cite
|
Sign up to set email alerts
|

The pre‐transmembrane region of the human immunodeficiency virus type‐1 glycoprotein: a novel fusogenic sequence

Abstract: We have investigated membrane interactions and perturbations induced by NH(2)-DKWASLWNWFNITNWLWYIK-COOH (HIV(c)), representing the membrane interface-partitioning region that precedes the transmembrane anchor of the human immunodeficiency virus type-1 gp41 fusion protein. The HIV(c) peptide bound with high affinity to electrically neutral vesicles composed of dioleoylphosphatidylcholine, dioleoylphosphatidylethanolamine and cholesterol (molar ratio, 1:1:1), and induced vesicle leakage and lipid mixing. Infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
97
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 27 publications
5
97
0
Order By: Relevance
“…This region is proximal to a predicted TM domain (Figure 2A), which was identified using the WW octanol hydrophobicity scale that allows for the identification of TM helices of membrane proteins with very high accuracy (73). On the basis of these observations, it is unlikely that the aromatic domain is part of the TM anchor as previously predicted by Rota et al (6), rather, as described for the aromatic domains of HIV-1 and EboV (10,55,56,58), this region is most likely an independent domain proximal to the TM anchor of the S2 subunit.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…This region is proximal to a predicted TM domain (Figure 2A), which was identified using the WW octanol hydrophobicity scale that allows for the identification of TM helices of membrane proteins with very high accuracy (73). On the basis of these observations, it is unlikely that the aromatic domain is part of the TM anchor as previously predicted by Rota et al (6), rather, as described for the aromatic domains of HIV-1 and EboV (10,55,56,58), this region is most likely an independent domain proximal to the TM anchor of the S2 subunit.…”
Section: Resultsmentioning
confidence: 72%
“…Nieva and colleagues have shown that, for HIV-1 and EboV, this large region of high interfacial hydrophobicity is segmented into two independent domains: one aromatic amino acid rich segment at the C-terminal portion of this domain and an adjacent segment comprising the TM anchor of the fusion protein (10,55,56). The separation of this large region into two distinct domains is consistent with the observation that the C-terminal hydrophobic domains of these viral fusion proteins are considerably longer (35-40 amino acids) than the ∼20 amino acids required for a single R helix to span a membrane.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shortly thereafter, Suarez et al (18) reported on the ability of MPER peptides to associate with, permeabilize, and induce fusion between membranes. Since then, a number of membraneassociated MPER peptide structures have been resolved using NMR spectroscopy methods (19)(20)(21).…”
mentioning
confidence: 99%